Collimated blue and infrared beams generated by two-photon excitation in Rb vapor - Sell, J. F.; Gearba, M. A.; DePaola, Brett D.; Knize, R. J. (My University, 2014)
Utilizing two-photon excitation in hot Rb vapor we demonstrate the generation of collimated optical fields at 420 and 1324 nm. Input laser beams at 780 and 776 nm enter a heated Rb vapor cell collinear and circularly polarized, driving Rb atoms to the 5D[subscript 5∕2] state. Under phase-matching conditions coherence among the 5S[subscript 1∕2] → 5P[subscript 3∕2] → 5D[subscript 5∕2] → 6P[subscript 3∕2] transitions produces a blue (420 nm) beam by four-wave mixing. We also observe a forward and backward propagating IR (1324 nm) beam, due to cascading decays through the 6S[subscript 1∕2] → 5P[subscript 1∕2] states. Power saturation of the generated beams is investigated by scaling the input powers to greater than 200 mW, resulting in a coherent blue beam of 9.1mW power, almost an order of magnitude larger than previously achieved. We measure the dependences of both beams in relation to the Rb density, the frequency detuning between Rb ground-state hyperfine levels, and the input laser intensities.
Keywords: Rb vapor; Two-photon excitation; Collimated optical fields